Using the Objective Borderline Method (OBM) to support Board of Examiners' decisions in a medical programme. Issue 3 (4th May 2017) - Shulruf, Boaz; Booth, Roger; Baker, Heather; Bagg, Warwick; Barrow, Mark
Abstract: Decisions about progress through an academic programme are made by Boards of Examiners, on the basis of students' course assessments. For most students such pass/fail grading decisions are straightforward. However, for those students whose results are borderline (either at a pass/fail boundary or boundaries between grades) the exercise of some discretion by university staff is required. In the interests of the transparency of the exercise of this discretion and to increase the chances that the 'right' decision is made, we tested the validity of the second version of the Objective Borderline Method (OBM2) decision-making tool in a medical programme. Our results suggest that application of OBM2 provides valid data to help university staff make robust decisions about a student's progression through a programme, and with which to defend these decisions if that should be required.